Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Akuntansi Pengantar 2 Melalui Implementasi Model Pembelajaran Kooperatif Tipe STAD (Students Team Achievement Divisions). - Nova Novita (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2016)
ABSTRACT This study aims to find the way to improve learning outcomes at the course of Introduction to Accounting 2. Solution that offered by this research is implement one of the cooperative learning called Student Teams Achievement Division methods (STAD). There are two classes that teached by the researcher, then divided into class that implement the STAD method, while other were not implement any treatments method. After the midterm, both of classes then get the same treatment. The results showed that there are differences in the average learning outcomes of the class that applied the STAD method to the conventional method. The average value of midterm learning outcomes from the class that applied the STAD method is higher than the class who did not. In the period after the midterm, there is no mean difference between the two classes that have applied the STAD method. The test of before and after implementation the STAD method also showed that after implementation of STAD methods, student learning outcomes are better than before the implementation of STAD.The research findings are expected to be taken into consideration for the educational institutions to develop teaching methods that can improve the quality of students' understanding about the course of accounting.  Key words: learning method,Student Teams Achievement Division, cooperative learning, learning outcome